2022
DOI: 10.1086/718641
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation Stress Acts as Cause as well as Cost of Dispersal in Drosophila melanogaster

Abstract: 1. Environmental stress is one of the important causes of biological dispersal. At the same time, the process of dispersal itself can incur and/or increase susceptibility to stress for the dispersing individuals. Therefore, in principle, stress can serve as both a cause and a cost of dispersal.2. Desiccation stress is an environmentally relevant stress faced by many organisms, known to shape their population dynamics and distribution. However, the potentially contrasting roles of desiccation stress as a cause … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted May 31, 2024. ; https://doi.org/10.1101/2024.05.27.596025 doi: bioRxiv preprint these studies showed density dependent sex biased dispersal (Wang et al, 2014;Mishra et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The copyright holder for this preprint (which this version posted May 31, 2024. ; https://doi.org/10.1101/2024.05.27.596025 doi: bioRxiv preprint these studies showed density dependent sex biased dispersal (Wang et al, 2014;Mishra et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Here, we investigated this problem using laboratory populations of D. melanogaster, which has been a useful experimental model even for dispersal biology research (Dobzhansky and Wright 1943; Coyne et al, 1982, 1987; Tung et al, 2018a, 2018b; Dukas, 2020; Mishra et al, 2018, 2022). Importantly, most dispersal studies in D. melanogaster have used extreme starvation and/or desiccation driven movement of individuals to assess dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…Prior theoretical work has shown that when the costs of dispersal increase linearly with distance travelled, dispersal distributions could evolve to show peak probabilities of dispersal at intermediate distances from the source (Rousset and Gandon, 2002), i.e., non-monotonocity. Our selection apparatus requires dispersal to occur under desiccation (Mishra et al, 2022), which could form the basis of increasing costs with dispersal distance, although it is difficult to say whether or not this increase is likely to be linear. Such increasing costs could be exacerbated by larval malnutrition, suggesting further possibilities for the evolution of non-monotonic dispersal kernels.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we found significant detrimental effects of habitat type treatment on female progeny output as well as starvation resistance. Such negative effect of our habitat type treatment (viz., unstructured vs. structured) was unsurprising, and was a possibly a representation of hitherto reported cost of dispersal (Mishra et al, 2022). Though we did not record the degree of dispersal of individuals across the vials during our assay, we have ample data on the movement tendencies of flies under similar setups, and that using a two-patch system (see supplementary information for experimental details of dispersal tendency).…”
Section: Discussionmentioning
confidence: 99%
“…The assay was done under two habitat types – structured and unstructured. In addition to progeny production, we also measured starvation survival time as a measure of the survival component of fitness that is often affected by dispersal and reproduction (Salmon et al, 2001; Flatt, 2011; Harvanek et al, 2017; Mishra et al, 2022). The entire experiment was performed in a randomized block design with three independent statistical blocks using three randomly chosen replicate base populations (viz., BL 2 , Bl 3 and BL 4 ).…”
Section: Methodsmentioning
confidence: 99%